Analysis of constituents in different Fractions collected during distillation of Cardamom oil for flavour and fragrance applications - Biju K. Mani, Vinuthaa Murthy, Martin Boland, Kwang Yee (Journal of Applied Pharmaceutical Science, 2017)
Cardamom oil is used widely for flavouring in food, as medicine, in aromatherapy and as a taste enhancer in tobacco products as well as used in fragrance industry. Cardamom Oil is the essential oil of green cardamom fruit produced by steam distillation from the seeds after they've undergone a long drying and de-husking process. In the traditional distillation process, the oil collected on top of a separator half filled with water – as a whole. The main components contributing to flavour and fragrance properties of cardamom oil are alpha-pinene, eucalyptol, terpenes and a group of phenols occur at different stages and in different quantities during steam distillation. These components are released from the seeds during distillation based on its volatility. This study investigates the collection of cardamom oil in different fractions. Organoleptic as well as physical and chemical analysis including Gas Chromatograph and Mass Spectroscope shows that there is a clear fractionation of the components during distillation, which helps the end user to choose the right fraction based on what the cardamom oil is used for.
Keywords: Cardamom, Cardamom Oil, Essential oil, GC-MS, Eucalyptol, Gas Chromatograph, Mass spectroscopy.